(untitled) (Cambridge, U.K., 2003)
Represents an intellectual meeting of researchers to analyze how and why uncertainty affects American politics.
Keywords: Uncertainty,Sự không chắc chắn; Political aspects,Khía cạnh chính trị; United States,Nước Mỹ